Peran Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan - Syarifah Syarifah; Afifatul Hasanah (Jurnal Administrasi Pendidikan dan Konseling Pendidikan, 2020)
This study aims to determine how the role of the principal in improving the quality of education. This research focuses on the role of the principal or the principal's way of improving the quality of education. The method used in this study is the method of library research, where this research uses literature as an object. The data obtained were analyzed using content analysis techniques. The results show that the role of the principal is very important in improving the quality of education, with the leadership style used can be a reference in making the school that is led will be of quality and by involving the school community in all school activities.